[18F]Flutemetamol amyloid-beta PET imaging compared with [11C]PIB across the spectrum of Alzheimer’s disease - Hatashita, Shizuo; Yamasaki, Hidetomo; Suzuki, Yutaka; Tanaka, Kumiko; Wakebe, Daichi; Hayakawa, Hideki (European journal of nuclear medicine and molecular imaging, 2014)
Purpose The aim was to identify the amyloid beta (Aβ) deposition by positron emission tomography (PET) imaging with the 18 F-labeled Pittsburgh compound B (PIB) derivative [ 18 F]flutemetamol (FMM) across a spectrum of Alzheimer’s disease (AD) and to compare Aβ deposition between [ 18 F]FMM and [ 11 C]PIB PET imaging. Methods The study included 36 patients with AD, 68 subjects with mild cognitive impairment (MCI), 41 older healthy controls (HC) (aged ≥56), 11 young HC (aged ≤45), and 10 transitional HC (aged 46–55). All 166 subjects underwent 30-min static [ 18 F]FMM PET 85 min after injection, 60-min dynamic [ 11 C]PIB PET, and cognitive testing. [ 18 F]FMM scans were assessed visually, and standardized uptake value ratios (SUVR) were defined quantitatively in regions of interest identified on coregistered MRI (cerebellar cortex as a reference region). The PIB distribution volume ratios (DVR) were determined in the same regions. Results Of 36 AD patients, 35 had positive scans, while 36 of 41 older HC subjects had negative scans. [ 18 F]FMM scans had a sensitivity of 97.2 % and specificity of 85.3 % in distinguishing AD patients from older HC subjects, and a specificity of 100 % for young and transitional HC subjects. The [ 11 C]PIB scan had the same results. Interreader agreement was excellent (kappa score = 0.81). The cortical FMM SUVR in AD patients was significantly greater than in older HC subjects (1.76 ± 0.23 vs 1.30 ± 0.26, p < 0.01). Of the MCI patients, 68 had a bimodal distribution of SUVR, and 29 of them (42.6 %) had positive scans. Cortical FMM SUVR values were strongly correlated with PIB DVR ( r = 0.94, n = 145, p < 0.001). Conclusion [ 18 F]FMM PET imaging detects Aβ deposition in patients along the continuum from normal cognitive status to dementia of AD and discriminates AD patients from HC subjects, similar to [ 11 C]PIB PET.